Parental involvement in learning environment, social interaction, communication, and support towards children excellence at school - Ahmad, Nor Aniza; Hassan, Siti Aishah; Ahmad, Abdul Razaq; Chua, Lay Nee; Othman, Nor Hashim (School of Postgraduate Studies, Universitas Pendidikan Indonesia, 2017)
Role and parental involvement are important to produce excellence children in aspects of spiritual and physical. Malaysia Education Blueprint (2013-2025) through SARANA programme has been implemented at schools in Malaysia to increase involvement and participation of parents in giving support towards children excellence. Aim of study is to identify the level of parental involvement and support in learning. Parents Self-Assessment (PSA) has been distributed randomly to 391 parents during parents meeting at schools. Analysis of parental involvement focused on four main domains which are providing learning environment at home, social interaction with children, communication with children and support towards children excellence. Findings showed that providing learning environment at home (mean=0.78, s.d=0.23), social interaction with children (mean=5.40, s.d=1.63), and communication with children (mean=4.68, s.d=1.89) are at higher level mean score, while support towards children excellence show average mean score (mean=3.90, s.d=1.94). Implication of the study, support towards children excellence in praises, encouragement and guidance need to be improved by parents to help the school to increase achievement in education.